1992
DOI: 10.1128/iai.60.5.1952-1956.1992
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus antigen-induced eosinophil differentiation in a murine model

Abstract: Eosinophilia is a prominent feature of the cellular response in allergic and parasitic diseases. Allergic bronchopulmonary aspergillosis due to colonization of the lungs of some asthmatics with Aspergillusfumigatus is characterized by high levels of serum immunoglobulin E and peripheral blood (PB) and lung eosinophilia. This study investigates the role of eosinophils in the pathogenesis of allergic bronchopulmonary aspergillosis by using a mouse model. BALB/c mice were immunized intranasally and intraperitonea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…Blood eosinophils were counted after the last exposure to Af antigen. Peripheral blood was collected from the tail vein in tubes containing heparin (25 U/ml) and stained with Discombe's fluid (5 mg eosin Y dissolved in 1 ml acetone and further diluted to 20 ml with distilled water), as previously described (1,2). Tlie stained eosinophils were then counted with a hemacytometer.…”
Section: Kinetics Of Peripheral Blood Eosinophiliamentioning
confidence: 99%
See 2 more Smart Citations
“…Blood eosinophils were counted after the last exposure to Af antigen. Peripheral blood was collected from the tail vein in tubes containing heparin (25 U/ml) and stained with Discombe's fluid (5 mg eosin Y dissolved in 1 ml acetone and further diluted to 20 ml with distilled water), as previously described (1,2). Tlie stained eosinophils were then counted with a hemacytometer.…”
Section: Kinetics Of Peripheral Blood Eosinophiliamentioning
confidence: 99%
“…Eosinophil peroxidase was studied as a measure of eosinophil activity and was estimated in bonemarrow cells, as previously described (2,3,9). Briefly, 100 )il of bone-marrow cells (5xlO''/ml) from mice was cultured in complete RPMI 1640 medium in 96-well, sterile, round-bottom plates.…”
Section: Epo Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, only in a limited number of circumstances (e.g. responses to helminth parasites [8] or some fungal pathogens [9]) does degranulation appear to be a dominant effector function. A more expansive hypothesis suggesting that degranulation is a widely used and singularly important effector function whose ability to kill conveys an evolutionarily selective advantage to the host is problematic.…”
mentioning
confidence: 99%
“…[38][39][40][41] Exposure to A. fumigatus extracts leads to eosinopoiesis and the subsequent increase in peripheral blood eosinophils, reiterating that fungal antigens are responsible for the recruitment of eosinophils into the affected tissues. 42 In our previous studies we showed that prolonged exposure of OVA-sensitized and OVA-challenged rats to A. fumigatus spores resulted in enhanced levels of serum IgE, pulmonary eosinophils and bronchial hyper-responsiveness. 14,43 Although some authors reported accumulation of eosinophils following A. fumigatus inhalation, [44][45][46][47] in this study only a few eosinophils were observed after A. fumigatus exposure alone.…”
Section: Discussionmentioning
confidence: 95%